e-ScoutHix: Transforming Scouting Education in Junior High School through AI and Cultural Integration for Sustainable Character Development - Solihin, Annas; Kristanto, Andi; Gunansyah, Ganes; Daoyi, Zheng; Sijia, Sun (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study evaluates e-ScoutHix, an AI-based learning platform integrating ethnopedagogical principles into scouting education at Al Hikmah Full Day Junior High School, Surabaya. Designed to enhance student engagement with local cultural values, e-ScoutHix features interactive and personalized modules. Using a qualitative approach and survey data, the study examines validity, compatibility, usability, educational impact, clarity, and interactivity. The results show that e-ScoutHix is effective in increasing student engagement in scout learning, 85% of students reported higher engagement, and 90% of teachers observed improved social skills and cultural understanding. The platform effectively embeds values like gotong royong and sustainability, enriching the scout curriculum. e-ScoutHix enhances interactivity and fosters character development through a culturally relevant learning experience. This research highlights its potential for broader implementation as an inclusive, scalable, and sustainable technology-based education model, particularly in schools aiming to integrate cultural and ethical values into their curricula.